2012
DOI: 10.3791/3793
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Gynecologic Cancer

Abstract: Stereotactic body radiotherapy (SBRT) distinguishes itself by necessitating more rigid patient immobilization, accounting for respiratory motion, intricate treatment planning, on-board imaging, and reduced number of ablative radiation doses to cancer targets usually refractory to chemotherapy and conventional radiation. Steep SBRT radiation dose drop-off permits narrow 'pencil beam' treatment fields to be used for ablative radiation treatment condensed into 1 to 3 treatments.Treating physicians must appreciate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It may be envisioned that a second-line radiochemotherapy strategy could emerge for the management of incompletely responding persistent or recurrent ovarian cancers. Here, radiosurgery (41) could target and ablate sites of chemorefractory ovarian cancer while cabazitaxel provides radiosensitization and independent cytotoxicity. The combination of radiosurgery and concomitant chemotherapy (i.e., gemcitabine and carboplatin) is already being studied in a phase I clinical trial (listed at as NCT01652794).…”
Section: Discussionmentioning
confidence: 99%
“…It may be envisioned that a second-line radiochemotherapy strategy could emerge for the management of incompletely responding persistent or recurrent ovarian cancers. Here, radiosurgery (41) could target and ablate sites of chemorefractory ovarian cancer while cabazitaxel provides radiosensitization and independent cytotoxicity. The combination of radiosurgery and concomitant chemotherapy (i.e., gemcitabine and carboplatin) is already being studied in a phase I clinical trial (listed at as NCT01652794).…”
Section: Discussionmentioning
confidence: 99%
“…Fixed tungsten circular collimators (5–60 mm) or a tungsten-copper alloy iris aperture collimated a 6 MV radiation beam. For additional details, the reader is referred to a peer-reviewed, video-complemented algorithm for the three outpatient robotic SBRT treatment sessions (Kunos et al, 2012b). …”
Section: Methodsmentioning
confidence: 99%
“…Stereotactic radiosurgery has been evaluated in several retrospective studies of metastatic gynecological malignancies and has demonstrated activity at various doses and schedules. Particularly in patients with small tumor burden at recurrence and good performance status, the use of stereotactic body radiation therapy (SBRT) to treat FDG-PET avid para-aortic disease has shown a 4-year local control rate of 67.4%, with low incidence of G3-4 complications (Choi et al, 2009; Kunos et al, 2012a,b). More prospective studies are needed to confirm the role of molecular imaging as a routine examination during the follow-up of these patients (Elit et al, 2010).…”
Section: Evaluation Of Treatment Response and Disease Recurrencementioning
confidence: 99%